(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article deals with the poetics of the novels of Omon Mukhtor, one of the great representatives of modern Uzbek literature, the originality and composition of his works, the reflection of space and time, the harmony of epic and lyrical imagery, the absurd interpretation of reality.